2023
DOI: 10.1111/hae.14808
|View full text |Cite
|
Sign up to set email alerts
|

No immunological changes after factor VIII product switch: An in depth analysis in haemophilia A patients

Abstract: Background: A challenging complication in the treatment of haemophilia A is the formation of neutralizing anti-FVIII antibodies (inhibitors). There is ongoing debate on the effect of FVIII product and inhibitor risk, rendering patients and physicians reluctant to switch FVIII-products.Aim: This study aimed to evaluate changes in the immune profile of haemophilia A patients after switching FVIII products and their possible relation to inhibitor development. Secondary, FVIII efficacy after switching were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…There also appears to be discrepancy between half-life calculated using realworld and clinical trial data, for instance the lowest reported half-life for rFVIIIFc in this systematic literature review of 14.5 h was reported in a real-world study, 29 which is in line with a recently published real-world study reporting data on individuals switching to rFVIIIFc from SHL products (15.0 h). 30 One suggestion from Delavenne and Dargaud, 11 is to standardise PK studies, to ensure similar parameters are collected and to enable more accurate comparisons between studies; this approach is already in place for regulatory studies.…”
Section: Discussionmentioning
confidence: 99%
“…There also appears to be discrepancy between half-life calculated using realworld and clinical trial data, for instance the lowest reported half-life for rFVIIIFc in this systematic literature review of 14.5 h was reported in a real-world study, 29 which is in line with a recently published real-world study reporting data on individuals switching to rFVIIIFc from SHL products (15.0 h). 30 One suggestion from Delavenne and Dargaud, 11 is to standardise PK studies, to ensure similar parameters are collected and to enable more accurate comparisons between studies; this approach is already in place for regulatory studies.…”
Section: Discussionmentioning
confidence: 99%